Síntese e avaliação da atividade de alquilfenóis substituídos em Trypanosoma cruzi - Varela, Marina Themoteo [UNIFESP] (2018)
In this work the natural products gibbilimbol A and B isolated from Piper malacophyllum were used as prototypes for the development of structural analogues given their promising anti-Trypanosoma cruzi activity and low cytotoxicity. Initially, the addition of functional groups in the side chain of the phenol ring led to an increased antiparasitic activity as well as cytotoxicity. One hypothesis raised was that the cytotoxicity was associated with the presence of the phenol ring in these analogues. So, the new series proposed aims to study the importance of the phenols’ hydroxyl group and the oxygen atom in the para position of the ring, replacing it for a methoxy group or a hydrogen atom. Furthermore, disubstituted analogues, in meta and para positions, were proposed in order to evaluate how this would affect the activity and cytotoxicity. 18 analogues were synthetized and tested. Results showed that the monosubstituted amines were the most active in the series against both forms of the parasite and that the presence of the methoxybenzenic ring leads to a higher activity and lower cytotoxicity, when compared to other substitution patterns tested. Moreover, among the neutral analogues, disubstituted analogues showed activities lower than 10 μM for the replicative form of the parasite and a 20 fold selectivity index compared to mammalian cells.